Life-Saving Techniques in Nepalese Culture against Pandemic - Khatiwada, Som Prasad (Researcher: A Research Journal of Culture and Society, 2020)
Our ancestors were suffered from different kinds of the pandemic in the past. Like big natural disasters, big pandemic originated in each century killed millions of people on the earth. Our forefathers were familiar with such pandemics. Therefore, they developed the techniques of saving the lives of people inside the culture. Such techniques are popular as social rules, which were necessary to follow by the people of the society. For example, management of separate house for the kitchen and separate guest rooms is more scientific to control such pandemic. In the same way habits of cleaning hands, legs, and face after traveling outside the home relates to health as well as cultural behavior. The system of keeping a distance from other people is also culturally taught. Respecting people with joining hands or doing Namaste instead of shaking hands is our culture, which is very popular in the present pandemic period. Our forefathers developed such techniques and saved the lives of many people in the big pandemics period. Therefore, we need to explore such cultural habits and rules and follow them for the sake of saving lives in the present pandemic period.